Utilizing Blockchain Technology in Global Supply Chain Management: An Exploration of Scalable Information Systems - Syamsuddin; Saharuddin; Yusrizal; Dharmawati, Tuti; Fatmawati, Endang (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Global supply chain management is a critical component in the increasingly complex and connected world of modern business. In the era of globalization, companies face pressure to increase efficiency, transparency, and security in their supply chains. Blockchain technology has emerged as a potential solution to address some of these challenges by enabling more decentralized, transparent, and efficient supply chain management. However, the use of this technology in global supply chain management also raises several issues related to regulation, law, and collaboration with third parties. OBJECTIVE: This research then aims to explore the potential of blockchain technology in global supply chain management and understand the regulatory framework needed to support the implementation of this technology. METHOD: This research was carried out using a qualitative approach. The data used in this research comes from various research results and previous studies that are relevant to the discussion. RESULTS: The results of this research then found that the use of blockchain technology in global supply chain management promises to increase transparency, efficiency, and security. Smart contracts enable the automation of business processes, reducing costs and increasing visibility of operations. Collaboration with third parties is an important strategy in increasing supply chain efficiency. Regulation, data security, and international harmonization remain challenges. CONCLUSION: Defining the legal status of smart contracts and protecting data is key. Effective collaboration with third parties requires good communication and a mature strategy. With a deep understanding of blockchain technology and proper regulation, companies can maximize their benefits to create an efficient, transparent, and reliable supply chain.
Keywords: Blockchain; Supply Chain Management; Information Systems